2015
DOI: 10.1111/gwmr.12102
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Pressure Pulsing Reagent Delivery Approach

Abstract: Pressure pulsing technology is an innovative method that has been developed with the aim of overcoming preferred flow paths associated with remediation techniques that rely on the injection of reagents. Numerical and field experiments were conducted to assess how pressure pulsing affects groundwater flow and solute transport during reagent injection. A series of field experiments were performed at two field sites where a monitoring network designed to capture the breakthrough of solutes delivered from an injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The remaining contaminant mass exists as immobilized, disconnected pockets/blobs that remain trapped in diffusion‐controlled zones (Conrad et al ), or in lower permeability zones where contact with the injected reagent is hindered by heterogeneity (Parker et al ). In these zones, molecular diffusion ( D* ~10 −9 m 2 /s) is likely the primary transport mechanism responsible for bringing the injected reagent and contaminant together (Jose and Cirpka ; Gale et al ); however, diffusion is a slow process and contributes to inefficient mixing (Kitanidis and McCarty ). The remaining contaminant mass becomes a long‐term source that can lead to eventual rebound and persistence of dissolved plumes downgradient of the source zone (Thomson et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining contaminant mass exists as immobilized, disconnected pockets/blobs that remain trapped in diffusion‐controlled zones (Conrad et al ), or in lower permeability zones where contact with the injected reagent is hindered by heterogeneity (Parker et al ). In these zones, molecular diffusion ( D* ~10 −9 m 2 /s) is likely the primary transport mechanism responsible for bringing the injected reagent and contaminant together (Jose and Cirpka ; Gale et al ); however, diffusion is a slow process and contributes to inefficient mixing (Kitanidis and McCarty ). The remaining contaminant mass becomes a long‐term source that can lead to eventual rebound and persistence of dissolved plumes downgradient of the source zone (Thomson et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Gale et al. () also noted the potential capacity to overcome variations in hydraulic conductivity and a numerical simulation suggested that flow could be induced into lower permeability zones. These findings are consistent with the observations at the treatment site.…”
Section: Resultsmentioning
confidence: 99%
“…In a three‐and‐a‐half‐hour field test at the Canadian Forces Base Borden Site, Gale et al. () noted lower formation pressurization using pressure pulse technology compared with conventional injection, suggesting that a greater volume of treatment amendment can be added for a given bulk formation pressure. This occurred while yielding a more uniform advective profile.…”
Section: Resultsmentioning
confidence: 99%
“…Pressure pulsing technology (PPT) injects an aqueous solution via quick releases of a pressurized solution (Gale et al 2015). In theory, pressure perturbations create a sudden increase in fluid pressure (for fluids with low compressibility), momentarily dilating porous media pores in response to the pressure wave, thereby enhancing movement of the injected solution.…”
Section: Subsurface Access Methodsmentioning
confidence: 99%